102. Enhanced cognitive control in healthy aging revealed by increased prefrontal bioelectrical activity to the Stroop task. Issue 4 (April 2016) - Amato, N.; Nossa, A.; Magnani, G.; Martins-Silva, A.; Martinelli, V.; Comi, G.; Leocani, L.
Abstract : Healthy aging is associated with processing slowing, reduced executive functions, and reduced efficiency of inhibitory mechanisms. Aim of this study was to investigate the effects of aging on bioelectrical activity and processing speed to Stroop test, assessing frontal function. 23 younger and 19 older healthy subjects were included. Event-related potentials-ERPs were recorded with 29-channels during covert Stroop task performance, consisting in mental discrimination between congruent and incongruent colour names written in different colours. Manual reaction times (RTs) to the same stimuli were recorded separately. Group effects on RTs and ERPs latency were analysed using statistical multivariate analysis and ERPs source analysis was performed using low resolution brain electromagnetic tomography (LORETA). Compared with the younger group, older subjects had: (1) significantly slower RTs, but not decreased accuracy; (2) significantly delayed ERP late processing components with increased prefrontal source activation, but normal early afferent components. In conclusion, healthy aging mainly impacts higher order processing, rather than generalized visuomotor speed. Increased prefrontal activity suggests enhanced compensatory cognitive control or impaired intracortical inhibitory mechanisms.